Determinants of Immigrant Homeownership: Examining their Changing Role during the Great Recession and Beyond - Kusum Mundra; Ruth Uwaifo Oyelere (Institute for the Study of Labor (IZA), 2013)
The Great Recession had significant economic effects both in the U.S. and around the world. There is evidence that homeownership rates declined during this period, though some immigrants were less severely affected compared to natives. In this paper we investigate the role of several factors in reducing the vulnerability of immigrants in the face of the economic crisis and increasing the probability of their homeownership. Specifically we examine to what extent birthplace networks, savings, length of stay in the U.S., and citizenship status affect the probability of homeownership before the recession and to what extent these impacts have changed since the recession. Using data from Current Population Survey for the years 2000 - 2012 our results suggest that birthplace networks have a significant effect on homeownership and this effect further increases after the onset of recession. Moreover the impact of birthplace network on homeownership is stronger for citizens and those who are not recent immigrants. We also find a decline in the impact of saving and length of stay on the probability of homeownership during 2007-2012 compared to earlier years. In contrast we find an increase in the impact of being a citizen on immigrant homeownership during this period.
Keywords: R20; R23; J11; J15; 330; birthplace networks; home ownership; Great Recession; savings; years in the U.S.; citizenship status